2018
DOI: 10.4172/neuropsychiatry.1000379
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Daily Functional Performance and Relevant Factors in Patients with Alzheimer’s Disease and Subcortical Ischemic Vascular Disease

Abstract: ObjectiveTo compare daily functional performance and potential predictive factors in patients with Alzheimer's disease (AD) and subcortical ischemic vascular disease (SIVD). MethodsSixty-eight community patients with AD and 39 with SIVD were evaluated using the informantbased Barthel Index of Activities of Daily Living (B-ADL) and Instrumental Activities of Daily Living (IADL). Motor function, cognition, and white matter hyperintensities (WMHs) were assessed using the modified Rankin Scale (mRS), Cognitive Abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Based on the inverse correlation between mean ReHo values in the left ACG and the Trail Making Test A, lower ReHo values were linked with dampened neuronal activity that may consequently affect attention. This hypothesis could be further extrapolated to the mechanisms contributing to apathy (Tu et al, 2017a), executive dysfunction (Hsu et al, 2016), and gait problems (Tu et al, 2018a) commonly identified in patients with SIVD. An increase in ReHo values within the right ORB among the patients with AD provided an interesting parallel compared with the aforementioned distinct findings among the patients with SIVD.…”
Section: Distinct Degree and Spatial Coordinates Of Frontal Functionamentioning
confidence: 97%
“…Based on the inverse correlation between mean ReHo values in the left ACG and the Trail Making Test A, lower ReHo values were linked with dampened neuronal activity that may consequently affect attention. This hypothesis could be further extrapolated to the mechanisms contributing to apathy (Tu et al, 2017a), executive dysfunction (Hsu et al, 2016), and gait problems (Tu et al, 2018a) commonly identified in patients with SIVD. An increase in ReHo values within the right ORB among the patients with AD provided an interesting parallel compared with the aforementioned distinct findings among the patients with SIVD.…”
Section: Distinct Degree and Spatial Coordinates Of Frontal Functionamentioning
confidence: 97%